"For the services of shipwrights, coopers, and grumettas": Freetown's ship repair cluster in nineteenth-century Sierra Leone. (March 2023) - Everill, Bronwen
This article looks at the development of Sierra Leone's ship repair cluster, particularly focusing on the period 1780 to 1860. It argues that several factors contributed to the colony's ability to develop a ship repair cluster. The first was the local environment, which provided both a safe harbor for ships and boats, and local materials that could be used on European and American ships. Secondly, the port's increasing commercial role and its unique position as the site of the Courts of Mixed Commission for the adjudication of condemned slaving ships after the abolition of the slave trade gave ship's carpenters access to a wide and varied range of both customers and supplies. Finally, these material effects were enhanced by the cluster's effect on knowledge spillover and on-the-spot tacit knowledge creation as disruptions in the supply chain, competition with slave traders, and other local circumstances fostered innovation in Freetown's repair cluster.